PENGARUH KONDISI EKONOMI ORANGTUA DAN PERILAKU KONSUMTIF TERHADAP MOTIVASI BELAJAR KELAS XI IPS - Della Arum Mawarni, Della; Irmayanti, Elis; Prastyaningtyas, Efa Wahyu (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this study is to determine the effect of economic conditions and consumptive behavior on students' learning motivation. The research method uses a quantitative descriptive analysis approach with observational data collection techniques, interviews and questionnaires. Using saturated sampling technique. The analysis uses a Likert scale, and the analysis uses classical assumptions, multiple regression, t-test, and f-test. Findings (1) partially show that parents' financial status has a positive effect on learning motivation Sig. 0.009 <0.05, H_o is rejected, H_a is accepted, (2) partial consumption behavior on learning motivation has a positive effect on Sig. 0.029<0.05, H_o is rejected, H_a is accepted, (3) At the same time, the influence of parents' economic conditions and consumptive behavior on learning motivation has a positive effect on Sig. 0.001 < 0.05, H_o failed, H_alulus. it has been concluded that the economic conditions of parents and consumptive behavior have a positive effect on the learning motivation of students in class XI IPS SMAN 6 Kediri.